Comparative efficacy of active recovery and cold water immersion as post-match recovery interventions in elite youth soccer - Pooley, S.; Spendiff, O.; Allen, M.; Moir, H. J. (Journal of Sports Sciences, 2020)
The current study compared cold-water immersion (CWI) and active recovery (AR) to static stretching (SS) on muscle recovery post-competitive soccer matches in elite youth players (n = 15). In a controlled crossover design, participants played a total of nine competitive soccer games, comprising three 80 minute games for each intervention (SS, CWI and AR). Muscle oedema, creatine kinase (CK), countermovement jump performance (CMJA) and perceived muscle soreness (PMS) were assessed pre-, immediately post-, and 48 hours post-match and compared across time-intervals and between interventions. Following SS, all markers of muscle damage remained significantly elevated (P < 0.05) compared to baseline at 48 hours post-match. Following AR and CWI, CMJA returned to baseline at 48 hours post-match, whilst CK returned to baseline following CWI at 48 hours post-match only. Analysis between recovery interventions revealed a significant improvement in PMS (P < 0.05) at 48 hours post-match when comparing AR and CWI to SS, with no significant differences between AR and CWI observed (P > 0.05). Analysis of %change for CK and CMJA revealed significant improvements for AR and CWI compared to SS. The present study indicated both AR and CWI are beneficial recovery interventions for elite young soccer players following competitive soccer matches, of which were superior to SS.